The impact of rheumatoid arthritis on the risk of adverse events following joint replacement: a real-world cohort study - Burn E; Edwards CJ; Murray DW; Silman A; Cooper C; Arden NK; Prieto-Alhambra D; Pinedo-Villanueva R (Clinical Epidemiology, 2018)
Edward Burn,1 Christopher J Edwards,2 David W Murray,1 Alan Silman,1 Cyrus Cooper,1,3 Nigel K Arden,1,3 Daniel Prieto-Alhambra,1,4 Rafael Pinedo-Villanueva1,3 1Nuffield Department of Orthopaedics, Rheumatology and Musculoskeletal Sciences, University of Oxford, Oxford, UK; 2NIHR Wellcome Trust Clinical Research Facility, University Hospital Southampton, Southampton, UK; 3MRC Lifecourse Epidemiology Unit, Southampton University, Southampton, UK; 4GREMPAL Research Group, Idiap Jordi Gol and CIBERFes, Universitat Autonoma de Barcelona and Instituto de Salud Carlos III, Barcelona, Spain Purpose: To assess whether rheumatoid arthritis (RA) is associated with a greater risk of adverse events following total knee replacement (TKR) and total hip replacement (THR) than osteoarthritis (OA).Patients and methods: Individuals with a diagnosis of RA or OA were identified using primary care records. TKR and THR following diagnosis were identified using linked hospital records. Myocardial infarction (MI), prosthetic joint infection (PJI), venous thromboembolism (VTE), and death were identified within 90 days following surgery, and revision procedures over 10 years following surgery. The impact of RA compared to OA on the risk for these adverse events was assessed using Cox proportional hazard models. Univariable models, with diagnosis as the only explanatory variable, and multivariable models, with age, gender, and year of surgery first added and then a measure of other comorbidities also included, were estimated.Results: In all 20,763 individuals, with 10,260 TKR and 10,961 THR, were included in the analysis. Compared to those with OA, individuals with a diagnosis of RA had a greater incidence of MI over 90 days following TKR (OA: 0.28%, RA: 0.75%) and revision over 10 years following THR (OA: 5.55%, RA: 8.68%). Both of these differences were statistically significant with, for example, hazard ratios of 3.54 (1.44 to 8.73) for MI and 1.61 (1.06 to 2.46) for revision after controlling for age, gender, year of surgery, and other comorbidities.Conclusion: These findings suggest that, compared to individuals with OA, those with RA have an increased short-term risk of MI following TKR. While risk of MI remains below 1%, this does underline the importance of the management of cardiovascular risk factors for those with RA. RA was also associated with an increased long-term risk of revision following THR, which strengthens the argument for investing in therapies which may prevent the need for joint replacement. Keywords: hip, knee, arthroplasty, osteoarthritis, surgery